2022
DOI: 10.7759/cureus.23709
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Causing Necrotizing Granulomatous Lymphadenitis

Abstract: Localized necrotizing granulomatous lymphadenitis (GLA) is a very rare presentation of herpes simplex virus (HSV) infection. We are reporting a case that required multidisciplinary expertise to confirm the diagnosis and effectively treat the patient. Our patient had a recent diagnosis of chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) and presented with hematuria and palpable inguinal lymph nodes. Affirmative diagnosis required a core biopsy of the lymph node with immunochemistry staining and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These clues support the synapse, a key site where the functional connection between neurons occurs ( Faria-Pereira and Morais, 2022 ), whose information transmission was in chaos post infection. Alterations in synaptic signaling, in the release of neurotransmitters from presynaptic neurons, changes in binding to postsynaptic receptors, and synaptic degeneration are evident in the course of many neurodegenerative diseases ( Parmar et al., 2022 ; Peng et al., 2022 ; Wang et al., 2022a ). Indeed, we found that several differentially expressed proteins were involved in the pathways of KEGG associated with neurodegenerative diseases, autophagy, and other signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These clues support the synapse, a key site where the functional connection between neurons occurs ( Faria-Pereira and Morais, 2022 ), whose information transmission was in chaos post infection. Alterations in synaptic signaling, in the release of neurotransmitters from presynaptic neurons, changes in binding to postsynaptic receptors, and synaptic degeneration are evident in the course of many neurodegenerative diseases ( Parmar et al., 2022 ; Peng et al., 2022 ; Wang et al., 2022a ). Indeed, we found that several differentially expressed proteins were involved in the pathways of KEGG associated with neurodegenerative diseases, autophagy, and other signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of Richter Transformation depends on the histological features but usually consists of aggressive chemotherapeutic regimens with the possibility of Hematopoietic Cell Transplantation (HCT) [8] , [9] . Lymphadenitis secondary to Herpes Simplex Viral (HSV) infection is an exceedingly rare condition, with less than 20 cases in CLL/SLL patients reported in the literature to date [10] , [11] , [12] , [13] , [14] , [15] . The clinical presentation of HSV lymphadenitis is characterized by sudden widespread or local lymphadenopathy combined with fevers and sweating, often causing suspicion for Richter Transformation.…”
Section: Introductionmentioning
confidence: 99%